A nylon material with good flame retardancy and high toughness and a preparation method thereof

By adding polyborosiloxane, flame retardant and antioxidant to the nylon material and adopting specific processing methods, the problems of poor toughness and flammability in low temperature and dry states are solved, and nylon materials with high toughness and good flame retardant properties are achieved.

CN119775764APending Publication Date: 2025-04-08QUANZHOU PEAK SHOES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411891618.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Nylon materials have poor toughness in low temperature and dry states, are prone to cracking and absorbing water, and are flammable.

Method used

By adding polyborosiloxane, flame retardant and antioxidant, and blending and granulating using equipment such as mixers and twin screw extruders, nylon materials with good flame retardant properties and high toughness are formed.

Benefits of technology

It significantly improves the flame retardant properties and toughness of nylon materials, prevents cracking, and improves the oxygen index and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of engineering plastic modification, and relates to a nylon material with good flame retardancy and high toughness and a preparation method thereof. The material comprises the following raw materials in parts by weight: 100 parts of nylon, 10.62-47.1 parts of a mixture, 6-11.25 parts of a flame retardant, and 0.25-0.67 parts of an antioxidant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of engineering plastic modification, and relates to a nylon material with good flame retardancy and high toughness and a preparation method thereof. Background Art

[0002] Nylon (polyamide, PA) has excellent mechanical properties, good self-lubrication and chemical resistance, and good processing performance. It is one of the engineering plastics with the largest output and the widest application range in the world. With the continuous improvement of performance and the increasing variety, the use of nylon is becoming more and more extensive. It is widely used in automobiles, machinery, electronic appliances, textiles and other fields.

[0003] However, in actual applications, nylon has defects such as poor toughness at low temperatures and in dry states, easy cracking and water absorption, and due to its low oxygen index, it is also easy to burn. Summary of the invention

[0004] Therefore, in view of the above problems, the present invention provides a nylon material with good flame retardancy and high toughness and a preparation method thereof.

[0005] To achieve the above purpose, the technical solution of the present invention is to provide a nylon material with good flame retardant properties and high toughness, including the following raw materials in parts by weight: 100 parts of nylon, 10.62-47.1 parts of mixture, 6-11.25 parts of flame retardant, and 0.25-0.67 parts of antioxidant.

[0006] A further improvement is that the mixture comprises: 10-40 parts of polyborosiloxane, 0.6-6.7 parts of silane coupling agent, and 0.02-0.4 parts of plasticizer.

[0007] A further improvement is that the ratio of the plasticizer to polyborosiloxane is 1:100-1:500, and the mass ratio of the silane coupling agent to polyborosiloxane is 1:6-1:15.

[0008] A further improvement is that the molar ratio of silicon atoms to boron atoms in the polyborosiloxane is 15:1-5:1.

[0009] A further improvement is that the flame retardant includes: 3.33-6.25 parts of phosphorus-based flame retardant and 2.67-5 parts of nitrogen-based flame retardant.

[0010] A further improvement is that the phosphorus-based flame retardant is diethyl aluminum hypophosphite.

[0011] A further improvement is that the nitrogen flame retardant is melamine cyanurate.

[0012] A further improvement is that the antioxidant is N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

[0013] A further improvement is that the plasticizer includes but is not limited to dimethoxyethylene glycol phthalate, triethylene glycol dipelargonate, and the like.

[0014] A further improvement is that the silane coupling agent includes but is not limited to γ-aminopropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-methacryloyloxy functional alkoxysilane, and the like.

[0015] A further improvement is that the nylon includes but is not limited to nylon 6, nylon 66, nylon 11, nylon 12 and the like.

[0016] A method for preparing a nylon material with good flame retardancy and high toughness comprises the following steps: S1. Weigh polyborosiloxane, silane coupling agent and plasticizer and mix them evenly with a kneader to form a mixture; S2, taking the mixture in step S1 and the flame retardant, antioxidant and nylon particles and melt-blending them in an internal mixer, cooling, and crushing them to form modified nylon crushed pieces; S3, taking the modified nylon crushed pieces in step S2 and putting them into a twin-screw extruder, melt-extrude them, and granulate them through a pelletizer.

[0017] A further improvement is that in the step S1, the kneading time is 30-45 minutes and the kneading temperature is 15°C-25°C.

[0018] A further improvement is that in step S2, the nylon particles are pre-dried in an oven for 3 hours at a temperature of 80°C-100°C.

[0019] A further improvement is that in step S2, the banburying time is 10-15 minutes and the banburying temperature is 195°C-260°C.

[0020] A further improvement is that in step S3, the extrusion temperature is 205°C-280°C.

[0021] The advantages and beneficial effects of the present invention are: 1. Polyborosiloxane is added to nylon. Polyborosiloxane has good impact resistance and can greatly improve the toughness of nylon materials. Flame retardants and antioxidants are also added. On the one hand, it can increase the oxygen index of nylon, and on the other hand, it can improve the flame retardant ability, thereby improving the flame retardant properties of nylon.

[0022] 2. Furthermore, the silicon and boron elements in the polyborosiloxane molecular chain are used in combination with diethylaluminum hypophosphite and melamine cyanurate to produce a synergistic flame retardant effect, effectively improving the flame retardant properties of nylon materials.

[0023] 3. Furthermore, the boron atoms in the Si-OB structure of the polyborosiloxane molecular chain can form B:O electron bridge pairs with oxygen atoms in adjacent chains. This is a special dynamically reversible weak physical cross-linking network that is in a dynamic process of continuous dissociation and re-formation. Therefore, it has special rheological properties and good viscoelasticity, especially under the action of external forces. It has significant strain rate sensitivity. When impacted by external forces, polyborosiloxane can store and disperse energy through conformational transitions and the breaking of B:O electron bridge pairs. It has good impact resistance and prevents nylon from cracking.

[0024] 4. Furthermore, since the Si element in the main chain of polyborosiloxane has a low surface energy, it can easily migrate to the surface of the material to form a silicon-containing protective layer, thereby improving the stability of the condensed phase, thereby improving the stability of nylon, preventing nylon from burning easily, and improving the flame retardant properties of nylon.

[0025] 5. Furthermore, the boron element in polyborosiloxane can produce substances such as boron oxide during combustion, forming a protective layer to isolate oxygen and heat, thereby enhancing the flame retardant properties of nylon. DETAILED DESCRIPTION

[0026] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention. Example 1

[0027] A nylon material with good flame retardancy and high toughness comprises the following raw materials in parts by weight: 100 parts of nylon, 10.62-47.1 parts of a mixture, 6-11.25 parts of a flame retardant, and 0.25-0.67 parts of an antioxidant.

[0028] In order to facilitate the production of the mixture, the mixture includes: 10-40 parts of polyborosiloxane, 0.6-6.7 parts of silane coupling agent, and 0.02-0.4 parts of plasticizer, the ratio of the plasticizer to polyborosiloxane is 1:100-1:500, and the mass ratio of the silane coupling agent to polyborosiloxane is 1:6-1:15.

[0029] In order to improve the impact resistance of nylon, prevent cracking, and enhance the toughness of nylon, the molar ratio of silicon atoms to boron atoms in the polyborosiloxane is 15:1-5:1.

[0030] In order to further enhance the flame retardant performance, the flame retardant includes: 3.33-6.25 parts of phosphorus flame retardant and 2.67-5 parts of nitrogen flame retardant; the phosphorus flame retardant is: diethyl aluminum hypophosphite; the nitrogen flame retardant is: melamine cyanurate.

[0031] In order to improve the oxygen index of nylon, the antioxidant is: N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

[0032] In order to facilitate the selection of plasticizers and enhance convenience, the plasticizers include but are not limited to dimethoxyethylene glycol phthalate, triethylene glycol dipelargonate, and the like.

[0033] In order to facilitate the selection of silane coupling agents and enhance convenience, the silane coupling agents include but are not limited to γ-aminopropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-methacryloyloxy functional alkoxysilane, and the like.

[0034] In order to facilitate the selection of nylon and enhance convenience, the nylon includes but is not limited to nylon 6, nylon 66, nylon 11, nylon 12 and the like.

[0035] A method for preparing a nylon material with good flame retardancy and high toughness comprises the following steps: S1. Weigh polyborosiloxane, silane coupling agent and plasticizer and mix them evenly with a kneader to form a mixture; S2, taking the mixture in step S1 and the flame retardant, antioxidant and nylon particles and melt-blending them in an internal mixer, cooling, and crushing them to form modified nylon crushed pieces; S3, taking the modified nylon crushed pieces in step S2 and putting them into a twin-screw extruder, melt-extrude them, and granulate them through a pelletizer.

[0036] In the step S1, the kneading time is 30-45 minutes, and the kneading temperature is 15° C.-25° C.

[0037] In step S2, the nylon particles are dried in advance in an oven, the drying time is 3 hours, and the drying temperature is 80° C.-100° C.

[0038] In step S2, the banburying time is 10-15 minutes, and the banburying temperature is 195° C.-260° C.

[0039] In the step S3, the extrusion temperature is 205°C-280°C. Example 2

[0040] Based on the technical solution of Example 1, a nylon material with good flame retardant properties and high toughness includes the following raw materials in parts by weight: 100 parts of nylon, 29.9 parts of polyborosiloxane, 3.3 parts of silane coupling agent, 0.06 parts of plasticizer, 0.4 parts of antioxidant, 4 parts of melamine cyanurate, and 3.3 parts of diethyl aluminum hypophosphite.

[0041] The nylon is nylon 6, the silane coupling agent is γ-aminopropyltrimethoxysilane, and the plasticizer is dimethoxyethylene glycol phthalate.

[0042] First, polyborosiloxane, γ-aminopropyl trimethoxysilane and dimethoxyethylene glycol phthalate were mixed at room temperature in a kneader for 0.5 hours; then nylon 6 particles were dried in an oven at 80°C for 3 hours; then the above mixture, diethyl aluminum hypophosphite, melamine cyanurate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine and nylon 6 particles were blended in an internal mixer at a temperature of 230°C for 15 minutes, then the blend was taken out of the internal mixer and cooled naturally, and crushed into flakes by a crusher. Finally, it was extruded and granulated by a twin-screw extruder, and the extruder box temperature was 230°C-250°C. Example 3

[0043] Based on the technical scheme of Example 1, a nylon material with good flame retardant properties and high toughness includes the following raw materials in parts by weight: 100 parts of nylon, 29.2 parts of polyborosiloxane, 4 parts of silane coupling agent, 0.13 parts of plasticizer, 4.67 parts of diethyl aluminum hypophosphite, 2.67 parts of melamine cyanurate, and 0.67 parts of antioxidant.

[0044] The nylon is nylon 66, the silane coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and the plasticizer is triethylene glycol dipelargonate.

[0045] First, polyborosiloxane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and triethylene glycol dipelargonate were mixed at room temperature in a kneader for 45 minutes; then nylon 66 particles were dried in an oven at 100°C for 3 hours; then the above mixture, diethylaluminum hypophosphite, melamine cyanurate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine and nylon 66 particles were blended in an internal mixer at 260°C for 10 minutes, then the blend was taken out of the internal mixer and cooled naturally, and crushed into flakes by a crusher. Finally, it was extruded and granulated by a twin-screw extruder, and the extruder box temperature was 240°C-275°C. Example 4

[0046] A nylon material with good flame retardancy and high toughness comprises the following raw materials in parts by weight: 100 parts of nylon, 21.2 parts of polyborosiloxane, 3.75 parts of silane coupling agent, 0.05 parts of plasticizer, 4.375 parts of diethyl aluminum hypophosphite, 5 parts of melamine cyanurate, and 0.25 parts of antioxidant.

[0047] The nylon is nylon 11, the silane coupling agent is gamma-methacryloyloxy functional group alkoxysilane, and the plasticizer is dimethoxyethylene glycol phthalate.

[0048] First, polyborosiloxane, γ-methacryloyloxy functional alkoxysilane, and dimethoxyethylene glycol phthalate are mixed at room temperature in a kneader for 25 minutes; then the nylon 11 particles are dried in an oven at 80°C for 3 hours; then the above mixture, diethyl aluminum hypophosphite, melamine cyanurate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine and nylon 11 particles are blended in an internal mixer at a temperature of 195°C for 12 minutes, and then the blend is taken out of the internal mixer and cooled naturally, and crushed into flakes by a crusher. Finally, the mixture is extruded and granulated by a twin-screw extruder, and the extruder box temperature is 190°C-205°C. Example 5

[0049] A nylon material with good flame retardancy and high toughness comprises the following raw materials in parts by weight: 100 parts of nylon, 20.56 parts of polyborosiloxane, 4.375 parts of silane coupling agent, 0.0625 parts of plasticizer, 6.25 parts of diethyl aluminum hypophosphite, 5 parts of melamine cyanurate, and 0.375 parts of antioxidant.

[0050] The nylon is nylon 12, the silane coupling agent is γ-aminopropyltriethoxysilane, and the plasticizer is triethylene glycol dipelargonate.

[0051] First, polyborosiloxane, γ-aminopropyl triethoxysilane and triethylene glycol dipelargonate are mixed at room temperature in a kneader for 30 minutes; then nylon 12 particles are dried in an oven at 80°C for 3 hours; then the above mixture, diethyl aluminum hypophosphite, melamine cyanurate, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine and nylon 12 particles are blended in an internal mixer at a temperature of 190°C for 15 minutes, then the blend is taken out of the internal mixer and cooled naturally, and crushed into flakes by a crusher. Finally, the mixture is extruded and granulated by a twin-screw extruder, and the extruder box temperature is 200°C-230°C.

[0052] The nylon samples prepared in Examples 2-5 were subjected to UL94 flammability test and compared with unmodified nylon, and the performance data were shown in Table 1:

[0053] Table 1 Flammability data of Example 2-5 nylon and unmodified nylon From the analysis of Table 1, it can be seen that the flame retardant grade of each example sample after modification reaches V0 grade, which is at least 2 grades higher than that of the unmodified nylon material, and the flammability is greatly reduced, thus achieving the intended purpose of the present invention.

[0054] The flame retardant toughened nylon particles obtained in Examples 2-5 and the unmodified nylon were dried at 100°C for 3 hours, and the dried flame retardant toughened nylon particles were respectively injection molded into notched impact test specimens that meet the national standard GB / T1843 and tensile test specimens that meet the national standard GB / T1040 by an injection molding machine. The notched impact performance and tensile mechanical performance tests of the prepared specimens were performed, and the obtained performance data are shown in the following table:

[0055] Table 2 Mechanical properties of nylon 6 in Example 2

[0056] Table 3 Mechanical properties of nylon 66 in Example 3

[0057] Table 4 Mechanical properties of nylon 11 in Example 4

[0058] Table 5 Mechanical properties of nylon 12 in Example 5 From the analysis of Tables 2-5, it can be seen that the impact strength of the modified samples of each embodiment is increased by about 2-4 times compared with the unmodified comparative example, which greatly improves the impact toughness of the nylon material, overcomes its defects such as poor dry toughness and easy cracking, and achieves the expected purpose.

[0059] In summary, the above flame retardant and mechanical property data show that the technical solution of the present invention is stable and reliable, achieves the established purpose of the invention, and solves the technical problems that have always existed in the relevant fields.

[0060] The above description of the present invention is only a partial embodiment, but the present invention is not limited to the above embodiment. The above embodiment is illustrative and not restrictive. All specific extensions of the materials and methods of the present invention, without departing from the scope of protection of the present invention and the claims, are within the scope of protection of the present invention.

Claims

1. A nylon material with good flame retardancy and high toughness, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of nylon, 10.62-47.1 parts of a mixture, 6-11.25 parts of a flame retardant and 0.25-0.67 parts of an antioxidant.

2. The nylon material with good flame retardancy and high toughness according to claim 1, characterized in that: The mixture comprises: 10-40 parts of polyborosiloxane, 0.6-6.7 parts of silane coupling agent, and 0.02-0.4 parts of plasticizer.

3. The nylon material with good flame retardancy and high toughness according to claim 2, characterized in that: The ratio of the plasticizer to polyborosiloxane is 1:100-1:500, and the mass ratio of the silane coupling agent to polyborosiloxane is 1:6-1:

15.

4. The nylon material with good flame retardancy and high toughness according to claim 2, characterized in that: The molar ratio of silicon atoms to boron atoms in the polyborosiloxane is 15:1-5:

1.

5. The nylon material with good flame retardancy and high toughness according to claim 1, characterized in that: The flame retardant comprises: 3.33-6.25 parts of phosphorus flame retardant and 2.67-5 parts of nitrogen flame retardant.

6. The nylon material with good flame retardancy and high toughness according to claim 5, characterized in that: The phosphorus-based flame retardant is diethyl aluminum hypophosphite.

7. The nylon material with good flame retardancy and high toughness according to claim 5, characterized in that: Nitrogen flame retardant: melamine cyanurate.

8. The nylon material with good flame retardancy and high toughness according to claim 1, characterized in that: The antioxidant is: N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

9. A method for preparing a nylon material having good flame retardancy and high toughness, characterized in that: The steps include: S1. Weigh polyborosiloxane, silane coupling agent and plasticizer and mix them evenly with a kneader to form a mixture; S2, taking the mixture in step S1 and the flame retardant, antioxidant and nylon particles and melt-blending them in an internal mixer, cooling and crushing them to form modified nylon crushed pieces; S3, taking the modified nylon crushed pieces in step S2 and putting them into a twin-screw extruder, melt-extrude them, and granulate them through a pelletizer.

10. The method for preparing a nylon material with good flame retardancy and high toughness according to claim 9, characterized in that: In the step S1, the kneading time is 30-45 minutes, and the kneading temperature is 15° C.-25° C.